Hanehalkı otomobil sahip olma durumunun ardışık logit modeli ile tahmini - Tümsel, Büşra (My University, 2016)
HANEHALKI OTOMOBİL SAHİP OLMA DURUMUNUN ARDIŞIK LOGİT MODELİ İLE TAHMİNİ Bu çalışmanın amacı, ardışık logit modeli tahmininden yararlanarak hanehalkının otomobil sahipliğini etkileyen faktörleri belirlemektir. Ardışık logit modelinin çoklu nitel tercih modellerinden farkı, bağımlı değişkeni oluşturan ikiden fazla seçeneğin ardışık yapıda ve her aşamada olasılığın hesaplanabilir olmasıdır. Her bir ardışık geçişin tercihinin olasılığı diğer olasılıklardan bağımsızdır. Bu çalışmada, Türkiye İstatistik Kurumu 2013 yılı Bütçe Anketi’ne katılanların tümü 9975, sürekli çalışan 3733 ve geçici veya sabit süreli sözleşmeli ve sözleşmesiz olarak arada sırada çalışan 618 hanehalkına ait bilgilerden yararlanılarak üç ayrı ardışık logit modeli incelenmiştir. Otomobil sahipliği ardışık bir yapıya sahip olduğu için hanehalkının otomobil sahipliğini ardışık logit modeli yardımıyla incelemek gerekmektedir. Model tahmini için hanehalkı reisinin cinsiyeti, mesleği, yaşı, çalıştığı süre, yıllık hanehalkının kullanılabilir geliri ve aylık harcamaları ele alınmıştır. Hanehalkının tümü ve sürekli çalışan hanehalkınına ait model tahmini sonucunda elde edilen bulgulara göre, hanehalkının otomobile sahip olmamasını en çok etkileyen değişkenin hanehalkının aylık harcamaları olduğu görülmüştür. Hanehalkının aylık harcamaları arttıkça arabaya sahip olma olasılığı azalmaktadır. İşverenin verdiği bir arabaya sahip olma olasılığını en çok etkileyen değişken hanehalkı reisinin mesleğidir. Profesyonel meslek mensubu olan hanehalkı reislerine işveren tarafından araç tahsil edilme ihtimali çok yüksektir. Hanehalkının kendisine ait bir arabaya sahip olma olasılığını en çok etkileyen değişken ise hanehalkının yıllık kullanılabilir geliridir. Hanehalkının yıllık kullanılabilir geliri arttıkça hanehalkının bir arabaya sahip olma olasılığı artmaktadır. Geçici veya sabit süreli sözleşmeli ve sözleşmesiz olarak arada sırada çalışan hanehalkına ait model tahmini sonucundan elde edilen bulgulara göre, hanehalkının otomobile sahip olmamasını en çok etkileyen değişken hanehalkının aylık harcamaları, işverenin verdiği bir arabaya sahip olma olasılığını en çok etkileyen değişken hanehalkının aylık harcamaları ve hanehalkının kendisine ait bir arabaya sahip olma olasılığını en çok etkileyen değişken ise hanehalkının yıllık kullanılabilir geliridir.

ESTIMATION OF HOUSEHOLD AUTOMOBILE OWNERSHIP USING SEQUENTIAL LOGIT MODEL The aim of this study is to identify the factors affecting the household automobile ownership by taking the advantage of estimation of sequential logit model. Sequential multi-choice model’s qualitative difference of the logit model is that the dependent variable has more than two consequtive work options and the probability which can be calculated at each stage. The probability of each successive transition is independent of other possibilities. In this study, 3 separate sequential logit models have been examined by using information which belongs to 618 households who work temporary or constant-timed contracted and who work occasionally without contract and 3733 households who work permanently among 9975 people who took place in 2013 budget survey of the Statistical Institute of Turkey. Because household automobile ownership has a sequential structure, it is necessary to examine automobile ownership with the help of sequential logit model. Gender of household head, profession, age, working time, annual household income which can be used, and monthly expenses are covered to estimate model. iv With regards to the estimated model result which belongs to all households and households who work permanently, household monthly expenditures are seen as the most affecting variable of not having an automobile. The more household spend monthly, the less possibility they have to own an automobile. The possibility of having an automobile provided by an employer is related to the occupation of household head. The household head who is a member of a professional occupation has a high probability of having a vehicle which is provided by an employer. Annual income being able to be used by household is the most affecting variable of probability of having an automobile which belongs to themselves. The more annual household income increases, the more probability of having an automobile household becomes. According to data which was provided from the results of estimated model of those who work temporarily or constanttimed contracted and work occasionally without contract, the variation which affects the possibility of not having automobile of households on their own most is monthly expenses of household; the most affecting variation for the possibility of having an automobile which is given to household by employer is monthly expenses of household, and the most affecting variation for automobile ownership possibility for households on their own is annual usable household income. Sequential Logit Model, Qualitative Choice Models, Automobile Ownership, Turkey
Keywords: Ekonometri